TINJAUAN YURIDIS TERHADAP TERJADINYA PENEMBAKAN PADA TAHAP PEMERIKSAAN KASUS TINDAK PIDANA TERORISME DIKAITKAN DENGAN ASAS PRADUGA TIDAK BERSALAH - Rafiqah Darwin; Erdianto Effendi; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
The principle of the presumption of innocence in the criminal procedure lawin effect in our country contains two purposes. First, to provide protection andguarantees for a human being who has been accused of committing a criminal actduring the case examination process so that his human rights are not raped.Second, to provide guidelines for officers to limit their actions in carrying out anexamination because it is a human being who has the same dignity and dignity asthe person conducting the examination.This type of research is normative juridical research. In this research, theresearcher discusses legal principles, namely the principle of the Presumption ofInnocence, which is the principle in which a person is considered innocent until acourt decision finds him guilty.The conclusions that can be obtained from the results of the research arefirst, actions taken by the police against the occurrence of shootings at the stageof investigating cases of criminal acts of terrorism according to the regulation ofthe National Police Chief and Police Chief, which is the Chief of PoliceRegulation Number 8 of 2009 concerning the Implementation of Human RightsPrinciples and Standards in Carrying Out Police Duties. The Republic ofIndonesia states that the use of firearms can only be used to protect human life.Then this contradicts the Standard operational procedure (SOP) for the use offirearms issued by the Police Criminal Investigation Unit. Second, the LegalImpact on Shootings at the Investigation Stage of Criminal Acts of TerrorismLinked to the Presumption of Innocence, it means the suspect is not necessarilyguilty. Because the right to declare someone guilty is only a court with a decisionthrough a valid legal process. The act was also carried out not in a state of forceddefense, even though the suspect also has the right not to be deprived of hisliberty, except in very special cases. Meanwhile, extrajudicial killings are carriedout not in a state of forced defense and there are also no laws and regulations thatjustify extrajudicial killings even though these acts are committed againstsuspected criminal acts of terrorism, which are included as extraordinary crimes.Keywords: Crime, Terrorism, Presumption of Innocence, Police.